Predictive brain: Addressing the level of representation by reviewing perceptual hysteresis. (August 2021) - Trapp, Sabrina; Pascucci, David; Chelazzi, Leonardo
Abstract: In recent years, the idea that the prediction of sensory input is one of the major computational goals of the nervous system led to the development of several large-scale theories of brain functioning, such as different versions of the Bayesian approach to brain functions, predictive coding theories of cognition and the Free-energy principle. During the years, various empirical phenomena have been re-interpreted within such frames, and have been considered as consequences of predictive processing. Here we focus on perceptual hysteresis, or serial dependence, as an exemplary case. We unravel a potential gap in the predictive frameworks and raise the idea that alternative explanations of this effect can solve this issue, as they address the type of cognitive and neural representations involved.